The Occurrence of Sulfated Salicinoids in Poplar and Their Formation by Sulfotransferase1. Issue 1 (25th February 2020) - Lackus, Nathalie D.; Müller, Andrea; Kröber, Tabea D. U.; Reichelt, Michael; Schmidt, Axel; Nakamura, Yoko; Paetz, Christian; Luck, Katrin; Lindroth, Richard L.; Constabel, C. Peter; Unsicker, Sybille B.; Gershenzon, Jonathan; et al.
Abstract : Sulfated salicinoids in poplar are produced by sulfotransferase1 and may function in sulfur homeostasis and plant defense. Abstract: Salicinoids form a specific class of phenolic glycosides characteristic of the Salicaceae. Although salicinoids accumulate in large amounts and have been shown to be involved in plant defense, their biosynthesis is unclear. We identified two sulfated salicinoids, salicin-7-sulfate and salirepin-7-sulfate, in black cottonwood ( Populus trichocarpa ). Both compounds accumulated in high amounts in above-ground tissues including leaves, petioles, and stems, but were also found at lower concentrations in roots. A survey of salicin-7-sulfate and salirepin-7-sulfate in a subset of poplar ( Populus sp.) and willow ( Salix sp.) species revealed a broader distribution within the Salicaceae. To elucidate the formation of these compounds, we studied the sulfotransferase ( SOT ) gene family in P . trichocarpa ( PtSOT ). One of the identified genes, PtSOT1, was shown to encode an enzyme able to convert salicin and salirepin into salicin-7-sulfate and salirepin-7-sulfate, respectively. The expression of PtSOT1 in different organs of P . trichocarpa matched the accumulation of sulfated salicinoids in planta. Moreover, RNA interference-mediated knockdown of SOT1 in gray poplar ( Populus × canescens ) resulted in decreased levels of sulfated salicinoids in comparison to wild-type plants, indicating that SOT1 is responsible for their formation in planta. The presence of a nonfunctional SOT1 allele in black poplar ( Populus nigra ) was shown to correlate with the absence of salicin-7-sulfate and salirepin-7-sulfate in this species. Food choice experiments with leaves from wild-type and SOT1 knockdown trees suggest that sulfated salicinoids do not affect the feeding preference of the generalist caterpillar Lymantria dispar . A potential role of the sulfated salicinoids in sulfur storage and homeostasis is discussed.